Hierarchically porous carbon derived from the activation of waste chestnut shells by potassium bicarbonate (KHCO3) for high‐performance supercapacitor electrode. (2nd December 2019) - Hong, Ping; Liu, Xu; Zhang, Xu; Peng, Sijia; Wang, Zidong; Yang, Yue; Zhao, Rongjun; Wang, Yude
Summary: 3D hierarchical porous carbon consisting of micropores, mesopores and macropores was successfully prepared through the activation of chestnut shell via KHCO3 . The influence of KHCO3 /chestnut shell ratio on the textural properties was carefully investigated and the structure, micrographs, and surface chemical status of the materials were expressed via X‐Ray diffraction (XRD), transmission electron micrographs (TEM), scanning electron microscope (SEM), X‐ray photoelectron spectroscopy (XPS), respectively. With the optimized amount of KHCO3, high specific pore surface area (2298 m 2 g ‐1 ) and high total pore volume (1.51 cm 3 g ‐1 ) were achieved, endowing an advantageous electrochemical characteristics for the electrode as ultracapacitors in three‐electrode system. At 2 A g ‐1, a high specific electric capacity of 387 F g ‐1 was reached. The remarkable electrochemical performances are mainly due to hierarchical porous structure with the high specific surface area (SSA) and the eminent total pore volume. It means that this hierarchical porous carbon prepared by activated by using KHCO3 would have more promising foreground in the field of energy storage.